Market reactions to accounting regulations in the savings and loan industry - Blacconiere, Walter G. (Journal of Accounting and Economics, 1991)
This paper addresses whether events leading to three regulatory accounting principles issued by the Federal Home Loan Bank Board affected the market value of Savings and Loan Associations (S&Ls). The market reaction to these regulations is predicted to be positive since they effectively eased minimum regulatory net worth requirements. A significant market reaction is observed for the regulation that allowed S&Ls to increase regulatory net worth by permitting appraised equity capital. However, results are inconsistent with the alternative hypothesis associated with the regulations permitting deferral of loan losses and net worth certificates.